Low-wage employment versus unemployment: Which one provides better prospects for women? - Mosthaf, Alexander; Schank, Thorsten; Schnabel, Claus (IZA Journal of European Labor Studies, 2014)
This study analyzes state dependence in low-wage employment of western German women using GSOEP data, 2000-2006. We estimate dynamic multinomial logit models with random eects and find that having a low-wage job increases the probability of being low-paid and decreases the chances of being high-paid in the future, in particular for low-paid women working part-time. However, concerning future wage prospects low-paid women are clearly better o than unemployed or inactive women. We argue that for women low-wage jobs can serve as stepping stones out of unemployment and are to be preferred to staying unemployed and waiting for a better jo
WiSo-Import:2015-08-12:2829